The Oval Office escape - Leavitt, Lindsey (Leavitt, Lindsey. Commander in Cheese, 2016)
"When Ava and Dean are sent to bring lunch to the mice who work in the Situation Room, they discover that the president's cat, Clover, is going to be spending a lot of time in the West Wing"--